1975
DOI: 10.1017/s0022172400024517
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaves and their dangers and safety in laboratories

Abstract: SUMMARYUsing a laboratory downward displacement vertical autoclave with the help of thermocouples recorded on a 12 point multichannel strip recorder, the risk of failing to sterilize laboratory discard buckets has been demonstrated. The use of proper temperature and time controls can prevent this risk.A load in a bucket with perforated sides is more easily sterilized than in a solid bucket. Wire baskets, where appropriate, facilitate the sterilizing practice. The addition of water to a bucket does not reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…and over is found to impair this property. Gillespie & Gibbons (1975) have commented on dangers of overheating media in laboratory autoclaves. Lesser degrees of heat sterilization may also prevent growth of small numbers of certain common pathogenic bacteria if faecal matter is not present.…”
Section: Discussionmentioning
confidence: 99%
“…and over is found to impair this property. Gillespie & Gibbons (1975) have commented on dangers of overheating media in laboratory autoclaves. Lesser degrees of heat sterilization may also prevent growth of small numbers of certain common pathogenic bacteria if faecal matter is not present.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results suggest that, rather than hastening air removal, the addition of water to a container prolongs the heat penetration time (Gillespie and Gibbons, 1975).…”
Section: The Containermentioning
confidence: 99%
“…Pressure steam sterilization is generally used to decontaminate biomedical waste before discarding it because it is practical, effective, and one of the less expensive ways of doing it (1,4). However, previous studies on the processing conditions required to obtain optimal waste decontamination have produced paradoxical results (3,4,6), making an optimal steam waste decontamination protocol difficult to establish.…”
mentioning
confidence: 99%
“…Researchers have previously reported that addition of water to bags before autoclaving did not decrease heat-up time (3,6). Others have reported paradoxical results (4).…”
mentioning
confidence: 99%